Usefulness of the Surprise Question on an Inpatient Oncology Service. (November 2018) - Singh, Sarguni; Rodriguez, Adrian; Lee, Darrell; Min, Sung-Joon; Fischer, Stacy
Background: Prognostication of survival in patients with advanced cancer has been challenging and contributes to poor illness understanding. Prognostic disagreement occurs even among providers and is a less studied phenomenon. Objective: We introduced the surprise question (SQ), "Would I be surprised if this patient died in the next 1 year, 6 months, and 1 month?, " at multidisciplinary rounds to increase palliative care referrals through the introduction of this prognostic prompt. Design, Setting, Patients: This quality improvement project took place from March 2016 to May 2016 on the medical oncology service at a tertiary academic medical center. The question was asked 3 times a week at multidisciplinary rounds which are attended by the hospital medicine provider, palliative care provider, and consulting oncologist. Primary oncologists and bedside nurses were also asked the SQ. Measurements: Referral rates to outpatient palliative care clinic, community-based palliative care clinic, inpatient palliative care consults, and hospice 3 months prior to, during, and 5 months postintervention. Results: Regular discussion of prognosis of patients with cancer in an inpatient medical setting did not increase referrals to inpatient or outpatient palliative care or hospice. Increased clinical experience impacted hospital medicine providers and bedside nurses' estimation of prognosis differently than oncology providers. Medical oncologists were significantly more optimistic than hospital medicine providers.